La cuarta hélice y la financiación de la innovación - Sierra, Jaime (2018)
Purpose: The purpose of this paper is to deal with the emerging relationship between civil society and the innovation system in Latin America and the Caribbean – the financing of innovation particularly – with the intention of suggesting a differentiated conceptual perspective and raising some of the most relevant questions presently. Approach: There is a structural disconnect between civil society and the world of innovation. However the exploration of the divergences between the neo-institutional and neo-evolutionist perspectives of the triple helix makes it possible to state that the evolution of funders in different contexts can generate an emerging articulation. The effects on the existing "systemness" particularly in Latin America and the Caribbean will depend to a large extent on the conceptual approach adopted and on its institutionalization in terms ofrestructuring the systemness of innovation systems and their governance. Findings: The evolution of the relationships between emerging financing mechanisms and innovative projects in Latin America and the Caribbean constitutes both an opportunity and a risk. If systemness is restructured the region could follow a path with high expectations; if traditional sub-dynamics persist the emerging phenomenon could be stripped of its full potential. Contribution: A different conceptual and practical analysis of the topic of financing innovation is proposed with emphasis on the Latin American and Caribbean case. Additionally research paths are suggested that reduce uncertainty about the relationship between the actors of the innovation system and civil society and its potential impact.